Salmonella enterica serovar Cerro displays a phylogenetic structure and genomic features consistent with virulence attenuation and adaptation to cattle - Cohn, Alexa R.; Orsi, Renato H.; Carroll, Laura M.; Liao, Jingqiu; Wiedmann, Martin; Cheng, Rachel A. (Frontiers in Microbiology, 2022)
Salmonella enterica subsp. enterica (S.) serovar Cerro is rarely isolated from human clinical cases of salmonellosis but represents the most common serovar isolated from cattle without clinical signs of illness in the United States. In this study, using a large, diverse set of 316 isolates, we utilized genomic methods to further elucidate the evolutionary history of S. Cerro and to identify genomic features associated with its apparent virulence attenuation in humans. Phylogenetic analyses showed that within this polyphyletic serovar, 98.4% of isolates (311/316) represent a monophyletic clade within section Typhi and the remaining 1.6% of isolates (5/316) form a monophyletic clade within subspecies enterica Clade A1. Of the section Typhi S. Cerro isolates, 93.2% of isolates (290/311) clustered into a large clonal clade comprised of predominantly sequence type (ST) 367 cattle and environmental isolates, while the remaining 6.8% of isolates (21/311), primarily from human clinical sources, clustered outside of this clonal clade. A tip-dated phylogeny of S. Cerro ST367 identified two major clades (I and II), one of which overwhelmingly consisted of cattle isolates that share a most recent common ancestor that existed circa 1975. Gene presence/absence and rarefaction curve analyses suggested that the pangenome of section Typhi S. Cerro is open, potentially reflecting the gain/loss of prophage; human isolates contained the most open pangenome, while cattle isolates had the least open pangenome. Hypothetically disrupted coding sequences (HDCs) displayed clade-specific losses of intact speC and sopA virulence genes within the large clonal S. Cerro clade, while loss of intact vgrG, araH, and vapC occurred in all section Typhi S. Cerro isolates. Further phenotypic analysis suggested that the presence of a premature stop codon in speC does not abolish ornithine decarboxylase activity in S. Cerro, likely due to the activity of the second ornithine decarboxylase encoded by speF, which remained intact in all isolates. Overall, our study identifies specific genomic features associated with S. Cerro’s infrequent isolation from humans and its apparent adaptation to cattle, which has broader implications for informing our understanding of the evolutionary events facilitating host adaptation in Salmonella.